Dialogic reader mindset in the novel by E. T. A. Hoffmann " The Life and Opinions of the Tomcat Murr" (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is dedicated to the study of the author′s dialogical aim at the reader in the novel «The Life and Opinions of the Tomcat Murr» by E. T. A. Hoffmann. The author says there are a lot of questions left without any answer, but the same time they are open filled connotations that have same sense. The task of the reader is to make these connotations clear and fill up the «gaps», that is, Hoffmann is a representative of the 19th century, but modeling the text, correspond to modern theories of reception.
Keywords: the novel; dialogical aim at the reader; the reader′s character; the real reader